Worldview Islam dalam Aktualisasi Moderasi Beragama yang Berkemajuan di Era Disrupsi Digital - Abdullah A Afifi; Afifi Fauzi Abbas (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2023)
The development of one's understanding will be very relevant to efforts to make improvements and changes. Worldview Islam means that Muslims use their religious understanding in actualizing progressive and constructive religious moderation which can balance the effect of digital disruption. Digital disruption has brought about an era filled with challenges, crises and threats. On the other hand, it provides hope, a great opportunity for the dissemination of knowledge, especially in the context of Muslims as agents of moderation and drivers of civilization. This article contains how Muslims need to formulate ways and future agendas to develop an Islamic worldview by enriching the tarjih method to actualize progressive religious moderation in an era of digital disruption in every sector. Digital disruption should be able to provide added value from the actualization of modern Muslims who are still able to align it with the guidelines from the al-Quran and as-Sunnah. Digital disruption should be able to become a medium for increasing public literacy towards the universal ethical values ??offered by Islam.